Being There for the Other: Towards a Phenomenology of Help in Mathematics - Karuku, Simon (University of Alberta, 2013)
A qualitative study, framed within a hermeneutic phenomenological stance, was undertaken to explore and describe the essence of the meaning of help in mathematics from the perspective of high school students. Participants were drawn from seven high schools located in the eastern and mid-eastern regions of Tanzania Mainland. The participants were asked to recall and describe a moment when they either sought or gave help in mathematics. Data were gathered through in-depth interviews and participants’ own written experiential accounts. According to the participants, seeking help in mathematics means seeking change in one’s mode of being in the mathematics life-world, and exhibiting responsive openness to the target of the seeking intention. This means that when students are seeking help, they are looking for someone who would help them experience conceptual change. Giving help, on the other hand, is more a way of being there for the recipient than a kind of doing. Most of the participants recalled and described a moment of seeking or giving the type of help that was ultimately aimed at improving the recipient’s performance in examinations. Accordingly, this thesis underscores the need for the seeking that has epistemological significance; namely, the seeking that is aimed at achieving conceptual understanding. In their lived-experience descriptions, many participants also shared feelings of being neglected and disobliged by their teachers. Although the participants longed for the teacher’s time, presence, attention, concern and care, these longings were not satisfied. This led to feelings of aloneness among the participants, which appear to have acted as an impulse for the participants to seek help in the sphere of peergroup relationships. However, due to the peers’ limitations in their ability to help each other, they felt the need to consult private tutors. As professional helpers, teachers play a critical role in transforming help-seeking moments into pedagogical moments. In this regard, one of the challenges raised in this thesis is the need to recover the notion of teaching as a vocation since in essence, it is those teachers who have been called to teaching that will express their being in and through the act of teaching.
A thesis submitted to the Faculty of Graduate Studies and Research in partial fulfillment of the requirements for the degree of Doctor of Philosophy Department of Secondary Education
Keywords: help; mathematics; high school; student-student relationship; teacherstudent relationship; phenomenology; private tutoring; Tanzania